2023
DOI: 10.1002/smll.202300859
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Engineering of NIR‐II/IIb Emitting AIEgen for Multimodal Imaging‐Guided Photo‐Immunotherapy

Abstract: In view of the great challenges related to the complexity and heterogeneity of tumors, efficient combination therapy is an ideal strategy for eliminating primary tumors and inhibiting distant tumors. A novel aggregation‐induced emission (AIE) phototherapeutic agent called T‐TBBTD is developed, which features a donor–acceptor–donor (D–A–D) structure, enhanced twisted molecule conformation, and prolonged second near‐infrared window (NIR‐II) emission. The multimodal imaging function of the molecule has significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Fluorescence imaging performed in the transparent second near-infrared (NIR-II, 1000–1700 nm) biowindow has recently been a powerful tool to directly visualize dynamic biological processes owing to its noninvasive damage control, real-time visualization, and high sensitivity and imaging resolution as well as deep tissue penetration and high signal-to-background ratio (SBR). So far, tremendous fluorophores emitting within the NIR-II region, including inorganic and organic NIR-II fluorophores, have been reported for various biological imaging applications. Notably, remarkable accomplishments have been made by organic NIR-II fluorophores due to their metal-free safety, ease of processability, and clinical translation. However, when these inherent hydrophobic fluorophores were fabricated into nanoparticles (NPs) with an aggregated state for biological applications, they always suffer from a low NIR-II quantum yield (QY) because of the emission quenching resulting from the strong intermolecular interactions, termed as the aggregation-caused quenching (ACQ) effect. Fortunately, as an alternative method, aggregation-induced emission (AIE), which was discovered by Tang et al, holds great potential to address the quenching problem. To drive emission to the NIR-II window, AIE luminogens (AIEgens) are usually designed as donor–acceptor–donor (D–A–D) structures with typical molecular motors to suppresses the strong intermolecular interactions. However, compared to the systematically well-explored near-infrared-I (NIR-I, 650–900 nm) AIEgens, the research on D–A–D-type NIR-II AIEgens received a snub, by contrast, owing to their lack of diversity and low AIE character (α AIE < 2, a value defined as the ratio of PL intensity at water fraction ( f w ) = 90% to that of f w = 0%), which has become a bottleneck in the bioimaging field. …”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence imaging performed in the transparent second near-infrared (NIR-II, 1000–1700 nm) biowindow has recently been a powerful tool to directly visualize dynamic biological processes owing to its noninvasive damage control, real-time visualization, and high sensitivity and imaging resolution as well as deep tissue penetration and high signal-to-background ratio (SBR). So far, tremendous fluorophores emitting within the NIR-II region, including inorganic and organic NIR-II fluorophores, have been reported for various biological imaging applications. Notably, remarkable accomplishments have been made by organic NIR-II fluorophores due to their metal-free safety, ease of processability, and clinical translation. However, when these inherent hydrophobic fluorophores were fabricated into nanoparticles (NPs) with an aggregated state for biological applications, they always suffer from a low NIR-II quantum yield (QY) because of the emission quenching resulting from the strong intermolecular interactions, termed as the aggregation-caused quenching (ACQ) effect. Fortunately, as an alternative method, aggregation-induced emission (AIE), which was discovered by Tang et al, holds great potential to address the quenching problem. To drive emission to the NIR-II window, AIE luminogens (AIEgens) are usually designed as donor–acceptor–donor (D–A–D) structures with typical molecular motors to suppresses the strong intermolecular interactions. However, compared to the systematically well-explored near-infrared-I (NIR-I, 650–900 nm) AIEgens, the research on D–A–D-type NIR-II AIEgens received a snub, by contrast, owing to their lack of diversity and low AIE character (α AIE < 2, a value defined as the ratio of PL intensity at water fraction ( f w ) = 90% to that of f w = 0%), which has become a bottleneck in the bioimaging field. …”
Section: Introductionmentioning
confidence: 99%
“…Constructing a donor–acceptor (D–A) structure is the major developing trend to prepare organic sensitizers with proper energy gap for efficient ROS generation. 27 Moreover, the energy gap can be well-modulated by incorporating appropriate acceptor and donor moieties. Even though the detailed mechanism is still not well-defined, it has been demonstrated that the lower excited energy enables the higher ROS generation ability of sonosensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these mechanisms requires a specific excitation wavelength that corresponds to the energy difference between the two energy levels at which the electron transition takes place. In semiconductors, this can be achieved by changing the effective band gap energy by doping due to the Moss Burstein effect 5 or by changing the composition, 6–8 while in molecules, the positions of the energy levels are modified by adding side groups 9 or changing the molecular configuration. 10 However, in all these cases, achieving a wide wavelength range that a NLA application can operate at various wavelengths is a formidable hurdle to overcome.…”
Section: Introductionmentioning
confidence: 99%